2010
DOI: 10.1016/j.bbagrm.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and divergent features of the structure and function of La and La-related proteins (LARPs)

Abstract: Genuine La proteins contain two RNA binding motifs, a La motif (LAM) followed by a RNA recognition motif (RRM), arranged in a unique way to bind RNA. These proteins interact with an extensive variety of cellular RNAs and exhibit activities in two broad categories: i) to promote the metabolism of nascent pol III transcripts, including precursor-tRNAs, by binding to their common, UUU-3'OH containing ends, and ii) to modulate the translation of certain mRNAs involving an unknown binding mechanism. Characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
219
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(230 citation statements)
references
References 155 publications
(255 reference statements)
10
219
0
1
Order By: Relevance
“…La-related proteins (LARPs), which contain a conserved La motif (LAM) domain and are normally immediately followed by a canonical RNA recognition motif (RRM) or noncanonical RRMlike (RRM-L) motif, are widely present in eukaryotes (Bayfield et al, 2010;Bousquet-Antonelli and Deragon, 2009). The co-evolving LAM-RRM/RRM-L regions are suggested to cooperate functionally for RNA (e.g., SnRNA and mRNA) binding activity (Bousquet-Antonelli and Deragon, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La-related proteins (LARPs), which contain a conserved La motif (LAM) domain and are normally immediately followed by a canonical RNA recognition motif (RRM) or noncanonical RRMlike (RRM-L) motif, are widely present in eukaryotes (Bayfield et al, 2010;Bousquet-Antonelli and Deragon, 2009). The co-evolving LAM-RRM/RRM-L regions are suggested to cooperate functionally for RNA (e.g., SnRNA and mRNA) binding activity (Bousquet-Antonelli and Deragon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analyses of the LAM region showed that the Arabidopsis genome harbors six LARP genes (LARP1a-1c and LARP6a-6c) (Bayfield et al, 2010;Bousquet-Antonelli and Deragon, 2009), but their biological functions have not been studied previously. Here, we report that overexpression of LARP1c led to premature leaf senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Although La is dispensable for growth in budding and fission yeast, La becomes essential in the presence of mutations that compromise the structure of essential pre-tRNAs or impair snRNP assembly (4,5). While many of the mutations cause the affected RNA to be degraded without La, Saccharomyces cerevisiae La is required for correct folding of pre-tRNA Arg CCG when the tRNA carries a mutation that weakens the anticodon stem, allowing formation of an incorrect helix.…”
mentioning
confidence: 99%
“…La binds the UUU OH that is the initial end of all RNA polymerase III transcripts and protects the RNAs from exonucleases (4,5). In budding yeast, La also binds processing intermediates of RNA polymerase II-transcribed small nuclear and nucleolar RNAs that end in UUU OH (6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation